The interdisciplinarity of the publications of the Medical University of Silesia in Katowice based on the analysis of the co-occurrence of issues specific to medicine and computer science - Ewelina Paluch; Marcela Mikulska (Managerial Economics)
Over the years, the study of the interdisciplinarity of publications has taken various forms, from its identification based on the disciplines represented by the authors, through the examination of citations used when writing the article, to the analysis of the publication text itself. The last of these approaches seems to be the most reliable in the context of verifying the real integration between disciplines in a specific text. The approach utilized in the conducted research facilitates a deeper analysis of integration not only between disciplines in general but also between specific issues within their domains, aiding the examination of the intensity of such connections. The research was aimed at analyzing publications affiliated with the Medical University of Silesia in Katowice in terms of their connection with issues included in the area of Computer Science. OpenAlex, a bibliographic database supported by data mainly from Scopus, WoS and Google Scholar, which uses concepts that make up the Wikidata knowledge base to describe the content of publications was used. A list of 14,136 publications from the Medical University of Silesia in Katowice was downloaded from the OpenAlex bibliographic database including such data as: publication id, title, author, abstract, journal, date of publication, ISSN number or concepts. Overall, the most prevalent concepts in the publications were concepts regarding the field of the medicine (medicine, internal medicine, cardiology). The most prevalent concepts concerning computer science in the publications were: computer science, logistic regression and artificial intelligence. The strenght of the connections between concepts regarding medicine and computer science was calculated by calculating the arithmetic mean of the score value for each pair of IT and medical concepts contained in a single publication. The study showed the importance of computer Science issues in the medical publications and highligted the growing importance of AI in the field of medicine.